Hubungan Perilaku dan Faktor Internal Paramedis dengan Kepatuhan pada SOP Pengelolaan Limbah Medis di RSUD Waru Pamekasan - Afriyani Noviyana; Tiwi Yuniastuti; Septia Dwi Cahyani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The amount of medical waste generated by healthcare facilities is increasing, due to the increasing number of hospitals, health clinics, health laboratories, and other treatment centers. Improper medical waste management can compromise the health and safety of patients and healthcare workers, necessitating medical waste management in accordance with applicable SOPs. This study generally aims to analyze the relationship between paramedic behavior and internal factors and compliance with SOPs for medical waste management at Waru Pamekasan Regional Hospital. This study was a quantitative cross-sectional design, with a population of 49 and a sample of 44 individuals obtained through simple random sampling. Univariate and bivariate analyses were used, with statistical tests using Chi-Square. The results indicate a relationship between paramedical attitudes and compliance with medical waste management SOPs. There was no relationship between paramedical knowledge, age, length of service, and education level with compliance with medical waste management SOPs at Waru Pamekasan Regional Hospital. It can be concluded that there is a relationship between paramedical attitudes and compliance with medical waste management SOPs. There was no relationship between paramedic knowledge, age, length of service, and education level with compliance with medical waste management SOPs at Waru Pamekasan Regional Hospital. Therefore, regular training on medical waste management SOPs, internal supervision, and the implementation of rewards and punishments are needed to improve paramedic compliance with medical waste management SOPs.